2019
DOI: 10.1002/hep.30140
|View full text |Cite
|
Sign up to set email alerts
|

Lect2 Controls Inflammatory Monocytes to Constrain the Growth and Progression of Hepatocellular Carcinoma

Abstract: our findings have demonstrated that LECT2 is an key player of liver tumorigenesis as its absence reshapes the TME and the tumor phenotype revealing LECT2 as a promising immunotherapeutic option for HCC. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 43 publications
3
35
0
Order By: Relevance
“…Apart from OPN, the role of LECT2, SLC10A1, CYP3A4, and HSD17B13 are also characterized in HCC. LECT2 (Leukocyte cell-derived chemotoxin 2) is originally identified as a chemotactic factor for neutrophils and stimulates the growth of chondrocytes and osteoblasts and acts as a tumor suppressor in HCC by multiple mechanisms, such as inactivation of MET, controlling inflammatory monocytes, and inhibition of VEGF165/VEGFR2-dependent signaling [41][42][43]. Downregulated SLC10A1 is correlated with poor post-surgery survival rate and larger tumor tissue mass in HCC patients and ectopic expression of NTCP significantly suppresses HCC cell proliferation [44].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from OPN, the role of LECT2, SLC10A1, CYP3A4, and HSD17B13 are also characterized in HCC. LECT2 (Leukocyte cell-derived chemotoxin 2) is originally identified as a chemotactic factor for neutrophils and stimulates the growth of chondrocytes and osteoblasts and acts as a tumor suppressor in HCC by multiple mechanisms, such as inactivation of MET, controlling inflammatory monocytes, and inhibition of VEGF165/VEGFR2-dependent signaling [41][42][43]. Downregulated SLC10A1 is correlated with poor post-surgery survival rate and larger tumor tissue mass in HCC patients and ectopic expression of NTCP significantly suppresses HCC cell proliferation [44].…”
Section: Discussionmentioning
confidence: 99%
“…Shom Goel et al recently found that CDK4/6 inhibitors could promote tumor immunogenicity and may have synergistic effects with immunotherapy . It was reported that the downregulation of LECT2 fostered the accumulation of inflammatory monocytes, which harbor immunosuppressive properties, and promoted the progression of hepatocellular carcinoma . PD1 is mainly expressed on effector T cells in tumor tissues in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…As an aggressive malignancy, HCC is characterized by high recurrence rate and mortality. With accumulating deep sequencing results, substantial amounts of ncRNAs are reported to be dysregulated in HCC (Liu et al, 2019; L'Hermitte et al, 2019). However, few studies have explored the role of circRNAs in HCC.…”
Section: Discussionmentioning
confidence: 99%